An alternative method for determining critical success factors of information system project - Subiyakto, A'ang; Ahlan, Abdul Rahman; Sukmana, Husni Teja (Universitas Ahmad Dahlan (UAD) and Institute of Advanced Engineering and Science (IAES), 2014)
Historically, information system (IS) researchers have been determining critical success factors (CSFs) since the 1970s. Meanwhile, most of them have also been performing inductively the CSFs determination in their IS project performance studies. Definitely, each of both methods has strengths and weaknesses, but we argue that researchers and practitioners will get an alternative choice if the methods are combined to share characteristics. This study has conducted to respond this issue through combination of the abovementioned CSFs determination methods to improve the result validity. It contributes into the debates on ensuring interrelationship between the IS project success criteria and their CSFs, incorporating the new factors, decomposing complexity of the project, and understanding focus of the stakeholders in the IS project environment. Although, the proposed method has only a combination method, but its implementation feasibility will be a good reference point for the upcoming studies especially in the CSFs determination method selection.